Analisis dan Implementasi Anupubbīkathā dalam Kurikulum Sekolah di Era Globalisasi - Arya Whisnu Karniawan; Kartika Joswidjaja (Jurnal Maitreyawira, 2021)
ABSTRACT Entering the era of globalization makes the world like a small village. The current of globalization provides a lot of information, an example is the Buddhist education. Since Buddhism returned to Indonesia, Buddhist education has developed a lot. However, the current education of Buddhism is not sufficient, as evidenced by the number of children who claim to be Buddhists but their religious knowledge is minimal. This is very unfortunate, because this limitation means that the Buddha's Teachings cannot be described precisely so that it does not reveal the purpose of Buddhism itself. For this reason, it is necessary to have appropriate and gradual teaching methods, starting from easy to difficult material. That is why Buddhism must of course be studied in stages. This gradual teaching formula is known as Anupubbikatha. Through this research, we can see the discussion of Anupubbikatha according to the Pali Tipitaka to clarify the teachings of Buddhism in this era of globalization as well as contextually applicable solutions to be implemented in the Buddhist religious education curriculum. The limitations of this research are still based on the basic theories contained in the Pali Tipitaka and the implications of the sources. This research can be used as a reference and a foundation for further research to see the extent and how the implementation of this Anupubbikatha thematic in a teaching curriculum. The scope of this research is limited to studying the appropriate and gradual teaching materia ls of Buddhism based on the Pali Tipitaka, reviewing each of its points in detail, along with the solutions for its application so that it can be applied in the world of education.